Bahasa Inggris - Mutiara Rizqa Chairunnisa; Fajrina Margareth Viruliana (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2022)
Communication in the family is an important factor in determining the good or bad attitude of children. Parents play an important role in educating their children. In the Koran there are many communication between parents and children, one of which is communication between the prophet Abraham and his son, the prophet Ismail. The story of the prophet Ibrahim and the prophet Ismail is a good example for parents and children to be able to communicate well while still prioritizing the aspect of obedience to Allah SWT. This is stated in Q.S As-Saffat:102. This study uses the theory of family communication patterns with descriptive research methods. The findings of this study found that there are ethical aspects of Islamic communication carried out by the prophet Ibrahim and the prophet Ismail, and the pattern of communication carried out is authoritative.